Positive electrode active material and battery

By using lithium composite oxides with a specific layered structure and particle size range as the positive electrode active material, the problem of insufficient battery capacity and reduced capacity during fast charging in the prior art is solved, and a battery with high capacity and excellent output characteristics is achieved.

CN112054169BActive Publication Date: 2025-02-28PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202010473929.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-05
Filing Date
2020-05-29
Publication Date
2025-02-28
Estimated Expiration
2040-05-29

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high-capacity batteries, especially when the capacity is reduced when it is fast charging.

Method used

The lithium composite oxide having a layered structure is used as the positive electrode active material. Specifically, the BET specific surface area of ​​the lithium composite oxide is 5 m2/g or more and 10 m2/g or less, the average particle size is 3 μm or more and 30 μm or less, and a multiphase mixture having a crystal structure of the space group C2/m and R-3m.

Benefits of technology

A high-capacity battery is realized, and the capacity reduction can be suppressed during fast charging and discharge, thereby improving the output characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112054169B_ABST
    Figure CN112054169B_ABST
Patent Text Reader

Abstract

The present disclosure provides a positive electrode active material and a high-capacity battery. The positive electrode active material of the present disclosure includes a lithium composite oxide having a crystal structure belonging to a layered structure. In the lithium composite oxide, the BET specific surface area is 5m 2 / g or more and 10m 2 / g or less, and an average particle size of 3 μm to 30 μm, and in the lithium composite oxide, an average crystallite size calculated by an X-ray diffraction method is #imgabs0# to #imgabs1#.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material for a battery and a battery. Background Art

[0002] Patent document 1 discloses a positive electrode active material for a secondary battery. The positive electrode active material comprises a core, a shell and a buffer layer, wherein the shell is arranged in a manner surrounding the core, and the buffer layer is located between the core and the shell, and comprises a three-dimensional network structure connecting the core and the shell and a void. The three-dimensional network structure in the core, the shell and the buffer layer each independently comprises a plurality of crystal grains having a chemical formula of Li a Ni 1-x-y Co x M1 y M3 z M2 w O 2 A polycrystalline lithium composite metal oxide represented by. The average crystal size of the grains is 50nm to 150nm. In Patent Document 1, in the above chemical formula, M1 contains any one or two or more elements selected from Al and Mn. M2 contains any one or two or more elements selected from Zr, Ti, Mg, Ta and Nb. M3 contains any one or two or more elements selected from W, Mo and Cr. a, x, y, z and w satisfy 1.0≤a≤1.5, 0<x≤0.5, 0<y≤0.5, 0.0005≤z≤0.03, 0≤w≤0.02 and 0<x+y≤0.7.

[0003] Prior Art Literature

[0004] Patent Document 1: Japanese Patent Application No. 2018-521456 Summary of the invention

[0005] In the prior art, it is desired to realize a high-capacity battery.

[0006] A positive electrode active material according to a technical solution of the present disclosure includes a lithium composite oxide having a crystal structure belonging to a layered structure.

[0007] In the lithium composite oxide, the BET specific surface area is 5m 2 / g or more and 10m 2 / g or less, and an average particle size of 3 μm or more and 30 μm or less,

[0008] In the lithium composite oxide, the average crystallite size calculated by X-ray diffraction is Above and the following.

[0009] The general or specific technical solutions of the present disclosure can be achieved through a positive electrode active material for a battery, a battery, a method, or any combination thereof.

[0010] According to the present disclosure, a high-capacity battery can be realized. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a cross-sectional view schematically showing a structure of a battery 10 as an example of a battery in the second embodiment.

[0012] Figure 2 This is a scanning electron microscope (SEM) image of the positive electrode active material in Example 1.

[0013] Description of Reference Numerals

[0014] 10. Battery

[0015] 11 Housing

[0016] 12. Positive electrode collector

[0017] 13. Positive electrode active material layer

[0018] 14 Partition

[0019] 15 Sealing plate

[0020] 16 Negative electrode collector

[0021] 17 Negative electrode active material layer

[0022] 18 Gasket

[0023] 21 Positive electrode

[0024] 22 Negative electrode DETAILED DESCRIPTION

[0025] Hereinafter, embodiments of the present disclosure will be described.

[0026] (Implementation Method 1)

[0027] The positive electrode active material in the first embodiment includes a lithium composite oxide having a layered crystal structure. In addition, the lithium composite oxide has a BET specific surface area of ​​5 m 2 / g or more and 10m 2 / g or less, and an average particle size of 3 μm or more and 30 μm or less, and an average crystallite size calculated by X-ray diffraction method in the lithium composite oxide is Above and the following.

[0028] According to the above technical configuration, a high-capacity battery can be realized.

[0029] The positive electrode active material in the first embodiment is, for example, a positive electrode active material for a lithium ion battery. When a lithium ion battery is constructed using the positive electrode active material in the first embodiment, the lithium ion battery has a redox potential (Li / Li) of about 3.4 V. + In addition, the lithium-ion battery generally has a capacity of more than 260 mAh / g.

[0030] The crystal structure belonging to the layered structure is, for example, a hexagonal crystal structure or a monoclinic crystal structure. In addition, specifically, the crystal structure belonging to the layered structure may be a crystal structure belonging to at least one of the space group C2 / m and the space group R-3m.

[0031] In the positive electrode active material of the first embodiment, the lithium composite oxide may include a first phase having a crystal structure belonging to the space group C2 / m and a second phase having a crystal structure belonging to the space group R-3m.

[0032] The crystal structure belonging to the space group C2 / m has a structure in which Li layers and transition metal layers (layers occupied by "cation elements such as transition metals") are alternately stacked. In addition to "cation elements such as transition metals", the transition metal layers may contain Li. Therefore, the crystal structure belonging to the space group C2 / m is different from the general existing material LiCoO 2 In comparison, it can store more Li in the crystal structure.

[0033] However, in the case of only a crystal structure belonging to the space group C2 / m, the barrier for movement of Li in the transition metal layer is high (ie, the diffusivity is low), so the capacity decreases during rapid charging.

[0034] On the other hand, in the crystal structure belonging to the space group R-3m, the diffusion path of Li exists two-dimensionally, and therefore the diffusivity of Li is high.

[0035] The lithium composite oxide contained in the positive electrode active material in Embodiment 1 may include phases having crystal structures respectively belonging to the above two space groups. In the case where the lithium composite oxide contained in the positive electrode active material in Embodiment 1 includes both a crystal structure belonging to the space group C2 / m and a crystal structure belonging to the space group R-3m, the positive electrode active material in Embodiment 1 can realize a high-capacity battery and a battery suitable for fast charging.

[0036] In addition, in the lithium composite oxide included in the positive electrode active material of Embodiment 1, a plurality of regions composed of the first phase and a plurality of regions composed of the second phase may be randomly arranged three-dimensionally.

[0037] According to the above technical configuration, the three-dimensional diffusion path of Li is enlarged, so more Li can be inserted and extracted, and a battery with a higher capacity can be realized.

[0038] In the positive electrode active material of Embodiment 1, the lithium composite oxide may be a multiphase mixture as described above. For example, a layer structure consisting of a single-phase main layer and a single-phase coating layer covering the main layer cannot correspond to a multiphase mixture in the present disclosure. In addition, a multiphase mixture refers to a substance containing multiple phases, and is not limited to mixing multiple materials corresponding to these phases during production.

[0039] The lithium composite oxide is a multiphase mixture, which can be confirmed by X-ray diffraction (XRD) measurement or electron beam diffraction measurement. Specifically, when a spectrum obtained for a lithium composite oxide contains peaks showing characteristics of multiple phases, the lithium composite oxide is determined to be a multiphase mixture.

[0040] The integrated intensity of each diffraction peak can be calculated, for example, using software attached to an XRD device (e.g., PDXL attached to a powder X-ray diffraction device manufactured by Rigaku Co., Ltd.). In this case, the integrated intensity of each diffraction peak can be obtained, for example, by calculating the area from the height and half-value width of each diffraction peak.

[0041] Furthermore, generally speaking, in an XRD pattern using CuKα radiation, in the case of a crystal structure belonging to space group C2 / m, the maximum peak of the diffraction angle 2θ in the range of 18° to 20° reflects the (001) plane. In addition, the maximum peak of the diffraction angle 2θ in the range of 20° to 23° reflects the (020) plane.

[0042] In addition, generally speaking, in the XRD pattern using CuKα rays, in the case of a crystal structure belonging to the space group R-3m, the maximum peak with a diffraction angle 2θ existing in the range of 18° to 20° reflects the (003) plane. In addition, there is no diffraction peak with a diffraction angle 2θ existing in the range of 20° to 23°.

[0043] In the case where the lithium composite oxide in embodiment 1 includes a first phase having a crystal structure belonging to space group C2 / m and a second phase having a crystal structure belonging to space group R3-m, it is not necessarily easy to completely determine the space group reflected by the maximum peak having a diffraction angle 2θ in the range of greater than 18° and less than 20°.

[0044] In this case, in addition to the above-mentioned X-ray diffraction measurement, a transmission electron microscope (TEM) can be used for electron beam diffraction measurement. By observing the electron beam diffraction pattern using a known method, in the positive electrode active material of embodiment 1, the space group of the lithium composite oxide can be determined. Thus, in the positive electrode active material of embodiment 1, it can be confirmed that the lithium composite oxide includes a first phase having a crystal structure belonging to the space group C2 / m and a second phase having a crystal structure belonging to the space group R-3m.

[0045] In addition, the lithium composite oxide in Embodiment 1 may be a two-phase mixture of the first phase and the second phase.

[0046] The positive electrode active material of Embodiment 1 has an integrated intensity ratio I of the second maximum peak existing in the range of a diffraction angle 2θ of 20° to 23° to the first maximum peak existing in the range of a diffraction angle 2θ of 18° to 20° in the XRD pattern of the lithium composite oxide. (20°-23°) / I (18°-20°) Can meet 0.05≤I (20°-23°) / I (18°-20°) ≤0.26.

[0047] Among them, I (20°-23°) / I (18°-20°) It is a parameter that can be an indicator of the existence ratio of the first phase and the second phase in the lithium composite oxide. (20°-23°) / I (18°-20°) In addition, if the proportion of the second phase increases, I (20°-23°) / I (18°-20°) Reduce.

[0048] Furthermore, in I (20°-23°) / I (18°-20°) When the ratio is 0.05 or more, the existence ratio of the first phase increases, so the amount of Li inserted and released during charge and discharge increases, thereby achieving a high capacity.

[0049] in I (20°-23°) / I (18°-20°) When the ratio is 0.26 or less, the existence ratio of the second phase increases, so the diffusibility of Li is improved, thereby achieving a high capacity.

[0050] As described above, the positive electrode active material of the first embodiment satisfies 0.05≤I in the lithium composite oxide. (20°-23°) / I (18°-20°) When ≤0.26, a large amount of Li can be inserted and extracted, and the diffusibility of Li is high. Therefore, the lithium composite oxide of Embodiment 1 can realize a high-capacity battery.

[0051] The lithium composite oxide contained in the positive electrode active material of Embodiment 1 may contain at least one selected from F, Cl, N, and S as described above.

[0052] According to the above technical configuration, by replacing a part of oxygen by electrochemically inert anions, the crystal structure is stabilized. In addition, by replacing a part of oxygen by anions with large ionic radius, the lattice is widened and the diffusivity of Li is improved. In addition, in the crystal having the first phase and the second phase as described above, the crystal structure is further stabilized. Therefore, more Li can be inserted and separated. Thus, a high-capacity battery can be realized.

[0053] In the positive electrode active material of Embodiment 1, the lithium composite oxide contains at least one element selected from F, Cl, N and S, so that the amount of oxygen redox does not become excessive. Therefore, the crystal structure is prevented from becoming unstable due to oxygen desorption, thereby improving the capacity and cycle characteristics.

[0054] In the positive electrode active material of Embodiment 1, the lithium composite oxide may contain F.

[0055] According to the above technical configuration, by replacing a part of oxygen by F with high electronegativity, the interaction between cations and anions is increased, and the discharge capacity or operating voltage of the battery is improved. In addition, by making F with high electronegativity solid solution, the electrons are localized compared with the case without F. Therefore, it is possible to suppress the oxygen detachment during charging, thereby stabilizing the crystal structure. In addition, in the crystal with the first phase and the second phase as described above, the crystal structure is further stabilized. Therefore, more Li can be inserted and detached. By combining these effects, a higher capacity battery can be achieved.

[0056] In the positive electrode active material of the first embodiment, the average particle size of the lithium composite oxide is in the range of 3 μm or more and 30 μm or less. When a battery is made using a lithium composite oxide as a positive electrode active material, high filling of the positive electrode active material is a means of increasing the capacity of the battery. In the positive electrode active material of the first embodiment, by using a large-particle lithium composite oxide having an average particle size in the above range as the positive electrode active material, high filling can be achieved and high capacity can be achieved.

[0057] Here, the average particle size of the lithium composite oxide in the positive electrode active material of the present disclosure is obtained by measuring the particle sizes of 100 lithium composite oxide particles using a scanning electron microscope (SEM) image and calculating the average value from the measured values.

[0058] As described above, when the lithium composite oxide has a large particle size, high filling can be achieved and high capacity can be achieved. However, when a lithium composite oxide having a large particle size such as an average particle size exceeding 30 μm is used as a positive electrode active material, the diffusion length of Li in the positive electrode active material increases, and a part of Li cannot contribute to the charge and discharge reaction. In the positive electrode active material of embodiment 1, the average particle size of the lithium composite oxide is less than 30 μm. Therefore, the positive electrode active material of embodiment 1 can suppress the capacity reduction even during rapid charge and discharge, and achieve high capacity.

[0059] In the positive electrode active material of the first embodiment, the average particle size of the lithium composite oxide may be 10 μm or more and 30 μm or less.

[0060] When the average particle size of the lithium composite oxide is 10 μm or more and 30 μm or less, the capacity can be further increased.

[0061] In the positive electrode active material of Embodiment 1, the average particle size of the lithium composite oxide may be 15 μm or more and 25 μm or less.

[0062] When the average particle size of the lithium composite oxide is 15 μm or more and 25 μm or less, the capacity can be further increased.

[0063] In the positive electrode active material of Embodiment 1, the BET specific surface area of ​​the lithium composite oxide is 5 m 2 / g or more and 10m 2 By using a lithium composite oxide having such a high specific surface area as a positive electrode active material, the Li diffusion length in the positive electrode active material is reduced, and the contact area with the electrolyte in the battery structure is increased. Therefore, a battery suitable for rapid charge and discharge can be realized.

[0064] In the positive electrode active material of the first embodiment, the BET specific surface area of ​​the lithium composite oxide may be 7.5 m 2 / g or more and 8.1m 2 / g or less.

[0065] The BET specific surface area of ​​the lithium composite oxide is 7.5 m 2 / g or more and 8.1m 2 / g or less, a high-capacity battery suitable for rapid charge and discharge can be realized.

[0066] In the positive electrode active material of Embodiment 1, the average crystallite size of the lithium composite oxide is Above and the following.

[0067] Here, in the positive electrode active material of Embodiment 1, the crystallite size of the lithium composite oxide can be calculated by taking the peak reflecting the (003) plane as a representative during XRD measurement using the Scherrer formula, etc. Furthermore, generally, when the oxide is calcined, the higher the calcination temperature, the narrower the diffraction line width, and the crystallite size increases isotropically.

[0068] The average crystallite size is determined by performing XRD measurement on five samples of the positive electrode active material of Embodiment 1 to determine the crystallite sizes of the lithium composite oxide, and calculating the average value thereof.

[0069] In the positive electrode active material of embodiment 1, the lithium composite oxide has both large particle size and high specific surface area. In such a lithium composite oxide, by satisfying the above range of average crystallite size, a battery with higher capacity and excellent output characteristics can be realized. In the case where the average crystallite size is too large, the Li diffusion length becomes longer, which is not conducive to high capacity. On the other hand, in the case where the average crystallite size is too small, the positive electrode active material cannot fully grow crystals, which is not conducive to high capacity. By satisfying the average crystallite size Above and As a result, the above-mentioned problem that is disadvantageous for increasing the capacity is unlikely to occur, and thus a battery having a high capacity and excellent output characteristics can be realized.

[0070] Here, as a comparative scheme, for example, a positive electrode active material described in Patent Document 1 is studied. The positive electrode active material described in Patent Document 1 has a core portion, a shell portion located around the core portion, and a buffer layer present in the gap between the core portion and the shell portion. Patent Document 1 discloses a lithium composite transition metal oxide, which is characterized in that, as a positive electrode active material, the BET specific surface area is 0.1 m 2 / g or above and 1.9m 2 / g or less, the average particle size (D50) is 2 μm or more and 20 μm or less, and the average crystallite size is 50 nm or more and 150 nm or less.

[0071] That is, the positive electrode active material described in Patent Document 1 does not realize a lithium composite oxide having both a large particle size that can be expected to be highly packed and a high specific surface area with excellent output characteristics, as in the positive electrode active material of Embodiment 1 of the present disclosure, nor does it provide any suggestion. That is, the positive electrode active material of Embodiment 1 is a technical structure that cannot be easily achieved based on the prior art to realize a high-capacity battery.

[0072] In addition, in the positive electrode active material of embodiment 1, the lithium composite oxide may contain, for example, at least one selected from Mn, Co, Ni, Fe, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si, P and Al as a "cation element such as a transition metal" other than lithium.

[0073] In addition, in the positive electrode active material of embodiment 1, the lithium composite oxide may contain, for example, at least one selected from Mn, Co, Ni, Fe, Cu, V, Ti, Cr and Zn, that is, at least one 3d transition metal element as the above-mentioned "cation element such as transition metal".

[0074] According to the above technical configuration, a battery with a higher capacity can be realized.

[0075] In the positive electrode active material of the first embodiment, the lithium composite oxide may contain at least one selected from the group consisting of Mn, Co, Ni and Al as the above-mentioned “cation element such as a transition metal”.

[0076] According to the above technical configuration, a battery with a higher capacity can be realized.

[0077] In the positive electrode active material of Embodiment 1, the lithium composite oxide may contain Mn.

[0078] According to the above technical configuration, by including Mn that is easily mixed with oxygen orbitals, oxygen detachment during charging is suppressed. In addition, in the crystal having the first phase and the second phase as described above, the crystal structure is further stabilized. Therefore, more Li can be inserted and detached. Thus, a battery with a higher capacity can be achieved.

[0079] Next, an example of the chemical composition of the lithium composite oxide in the positive electrode active material of the first embodiment will be described.

[0080] In the positive electrode active material of Embodiment 1, the average composition of the lithium composite oxide can be represented by the following composition formula (1).

[0081] Li x Me y O α Q β Formula (1)

[0082] Among them, Me can be at least one selected from Mn, Co, Ni, Fe, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si, P and Al.

[0083] In addition, Q may be at least one selected from F, Cl, N and S.

[0084] The composition formula (1) can satisfy the following conditions:

[0085] 1.05≤x≤1.5, 0.6≤y≤1.0, 1.2≤α≤2.0 and 0<β≤0.8.

[0086] According to the above technical configuration, a battery with a higher capacity can be realized.

[0087] Furthermore, in Embodiment 1, Me is composed of two or more elements (e.g., Me', Me''), and the composition ratio is "Me' y1 Me” y2 ”, “y=y1+y2”. For example, when Me is composed of two elements (Mn and Co), and the composition ratio is “Mn 0.6 Co 0.2 " In the case of "y = 0.6 + 0.2 = 0.8". In addition, when Q is composed of two or more elements, it can be calculated in the same way as the case of Me.

[0088] Furthermore, in the composition formula (1), when x is 1.05 or more, the amount of available Li increases, so the capacity is improved.

[0089] In addition, in the composition formula (1), when x is 1.5 or less, the available redox reaction of Me increases. As a result, it is not necessary to utilize a large amount of redox reaction of oxygen. As a result, the crystal structure is stabilized. Therefore, the capacity is improved.

[0090] In addition, in the composition formula (1), when y is 0.6 or more, the available redox reaction of Me increases. As a result, it is not necessary to utilize a large amount of redox reaction of oxygen. As a result, the crystal structure is stabilized. Therefore, the capacity is improved.

[0091] In the composition formula (1), when y is 1.0 or less, the amount of available Li increases, so the capacity is improved.

[0092] In the composition formula (1), when α is 1.2 or more, it is possible to prevent the charge compensation amount from decreasing due to the redox of oxygen, thereby improving the capacity.

[0093] In the composition formula (1), when α is 2.0 or less, excess capacity due to redox of oxygen can be prevented and the structure can be stabilized during Li desorption, thereby improving the capacity.

[0094] In the composition formula (1), when β is greater than 0, the structure is stabilized when Li is released due to the influence of the electrochemically inactive Q, thereby improving the capacity.

[0095] In the composition formula (1), when β is 0.8 or less, the influence of electrochemical inertness Q can be prevented from increasing, and the electron conductivity can be improved. Therefore, the capacity is improved.

[0096] Furthermore, the "average composition" of the lithium composite oxide of Embodiment 1 refers to the composition obtained by performing elemental analysis on the lithium composite oxide without considering the difference in the composition of each phase. Typically, it refers to the composition obtained by performing elemental analysis using a sample of the same or larger size as the primary particles of the lithium composite oxide. In addition, each phase (e.g., the first phase and the second phase) having a different crystal structure may have the same chemical composition or different chemical composition.

[0097] The above average composition can be determined by ICP emission spectroscopy, inert gas fusion-infrared absorption, ion chromatography, or a combination of these analytical methods.

[0098] In the composition formula (1), Me may contain at least one selected from the group consisting of Mn, Co, Ni, Fe, Cu, V, Ti, Cr and Zn, that is, at least one 3d transition metal element.

[0099] According to the above technical configuration, a battery with a higher capacity can be realized.

[0100] In the composition formula (1), Me may contain at least one selected from the group consisting of Mn, Co, Ni and Al.

[0101] According to the above technical configuration, a battery with a higher capacity can be realized.

[0102] In the composition formula (1), Me may contain Mn.

[0103] That is, Me may be Mn.

[0104] Alternatively, Me may include Mn and at least one element selected from Co, Ni, Fe, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si, P, and Al.

[0105] According to the above technical configuration, by including Mn that is easily mixed with oxygen orbitals, oxygen separation during charging is suppressed. In addition, the crystal structure is further stabilized in the crystal having the first phase and the second phase as described above. Therefore, a battery with a higher capacity can be achieved.

[0106] In the composition formula (1), the ratio of Mn to Me may be 59.9 mol% or more. That is, the molar ratio of Mn to the entire Me including Mn (Mn / Me ratio) may satisfy a relationship of 0.599 to 1.0.

[0107] According to the above technical structure, more Mn that is easy to mix with oxygen orbits can be included, thereby further suppressing oxygen separation during charging. In addition, the crystal structure is further stabilized in the crystal having the first phase and the second phase as described above. Therefore, a battery with a higher capacity can be achieved.

[0108] In the composition formula (1), Me may contain 20 mol % of at least one selected from B, Si, P and Al based on Me.

[0109] According to the above technical configuration, the structure is stabilized by including an element with a high covalent bond, so that the cycle characteristics are improved, thereby achieving a battery with a longer life.

[0110] In the composition formula (1), Q may contain F.

[0111] That is, Q can be F.

[0112] Alternatively, Q may contain F and at least one element selected from Cl, N and S.

[0113] According to the above technical configuration, by replacing a part of oxygen by F with high electronegativity, the interaction of cation-anion increases, and the discharge capacity or operating voltage of the battery is improved. In addition, by making F with high electronegativity solid solution, compared with the case of not containing F, the electron is localized. Therefore, it is possible to suppress the oxygen detachment during charging, so that the crystal structure is stabilized. In addition, as described above, in the crystal with the first phase and the second phase, the crystal structure is further stabilized. By these effects, a battery with higher capacity can be achieved.

[0114] In addition, the composition formula (1) may satisfy the following conditions:

[0115] 1.166≤x≤1.4 and 0.67≤y≤1.0.

[0116] According to the above technical configuration, a battery with a higher capacity can be realized.

[0117] In addition, the composition formula (1) may satisfy the following conditions:

[0118] 1.33≤α≤1.917 and 0.083≤β≤0.67.

[0119] According to the above technical configuration, it is possible to prevent excess capacity due to oxygen redox, and to stabilize the structure when Li is released by fully utilizing the influence of the electrochemically inactive Q. Therefore, a battery with a higher capacity can be realized.

[0120] In the composition formula (1), the ratio of "Li" to "Me" is represented by x / y.

[0121] The composition formula (1) may satisfy 1.39≤x / y≤2.0.

[0122] According to the above technical configuration, a battery with a higher capacity can be realized.

[0123] Furthermore, when x / y is greater than 1, for example, with the composition formula LiMnO 2 Compared with the conventional positive electrode active material shown in FIG.

[0124] In addition, when x / y is 1.39 or more, the amount of available Li is large and a diffusion path of Li is appropriately formed, thereby achieving a battery with a higher capacity.

[0125] In addition, when x / y is less than 2.0, it is possible to prevent the reduction of the redox reaction of available Me. As a result, it is not necessary to utilize a large amount of oxygen redox reaction. In addition, it is possible to prevent the crystal structure from becoming unstable when Li is separated during charging, and to prevent the Li insertion efficiency from decreasing during discharge. Therefore, a higher capacity battery can be achieved.

[0126] In addition, the composition formula (1) may satisfy 1.5≤x / y≤2.0.

[0127] According to the above technical configuration, a battery with a higher capacity can be realized.

[0128] In the composition formula (1), the ratio of "O" to "Q" is represented by α / β.

[0129] The composition formula (1) may satisfy 2≤α / β≤23.1.

[0130] According to the above technical configuration, a battery with a higher capacity can be realized.

[0131] Furthermore, when α / β is greater than 2, it is possible to prevent the reduction of charge compensation due to oxygen redox. In addition, the influence of electrochemical inertness Q can be reduced, so that electronic conductivity is improved. Thus, a battery with a higher capacity can be realized.

[0132] In addition, when α / β is less than 23.1, excess capacity due to oxygen redox can be prevented, and the structure is stabilized when Li is separated. In addition, by being affected by the electrochemically inert Q, the structure is stabilized when Li is separated. Therefore, a battery with a higher capacity can be achieved.

[0133] In the composition formula (1), the ratio of "Li+Me" to "O+Q" (that is, the ratio of "cation" to "anion") is represented by (x+y) / (α+β).

[0134] The composition formula (1) may satisfy 0.75≤(x+y) / (α+β)≤1.2.

[0135] According to the above technical configuration, a battery with a higher capacity can be realized.

[0136] Furthermore, when (x+y) / (α+β) is 0.75 or more, it is possible to prevent phase separation from occurring during synthesis and generation of a large number of impurities, thereby achieving a battery with a higher capacity.

[0137] In addition, when (x+y) / (α+β) is 1.2 or less, the amount of anion deficiency is small, and the crystal structure is stabilized when Li is released during charging, thereby achieving a higher capacity battery.

[0138] In addition, the composition formula (1) may satisfy 1.0≤(x+y) / (α+β)≤1.2.

[0139] According to the above technical configuration, a battery with a higher capacity can be realized.

[0140] In the positive electrode active material of the first embodiment, part of Li in the lithium composite oxide may be replaced by an alkali metal such as Na or K.

[0141] Furthermore, the positive electrode active material of the first embodiment may contain the above-mentioned lithium composite oxide as a main component (that is, the mass ratio relative to the entire positive electrode active material is 50% or more (50 mass % or more)).

[0142] According to the above technical configuration, a battery with a higher capacity can be realized.

[0143] Furthermore, the positive electrode active material of the first embodiment may contain the lithium composite oxide in an amount of 70% or more (70% by mass or more) relative to the entire positive electrode active material.

[0144] According to the above technical configuration, a battery with a higher capacity can be realized.

[0145] Furthermore, the positive electrode active material of the first embodiment may contain the lithium composite oxide in an amount of 90% or more (90% by mass or more) relative to the entire positive electrode active material.

[0146] According to the above technical configuration, a battery with a higher capacity can be realized.

[0147] Furthermore, the positive electrode active material of Embodiment 1 may include the above-mentioned lithium composite oxide and further include inevitable impurities.

[0148] In addition, the positive electrode active material of Embodiment 1 may include the above-mentioned lithium composite oxide and further include at least one selected from the group consisting of starting materials, by-products, and decomposition products used when synthesizing the positive electrode active material.

[0149] In addition, the positive electrode active material of the first embodiment may include only the above-mentioned lithium composite oxide except for impurities that are inevitably mixed, for example.

[0150] According to the above technical configuration, a battery with a higher capacity can be realized.

[0151] <Method for producing lithium composite oxide>

[0152] Hereinafter, an example of a method for producing the lithium composite oxide contained in the positive electrode active material of the first embodiment will be described.

[0153] In Embodiment 1, the lithium composite oxide can be produced, for example, by the following method.

[0154] First, a Me raw material and a basic compound are mixed and a coprecipitation reaction is performed at a pH of not less than 7 and not more than 8.5 to prepare a suspension containing precursor seed crystals containing Me.

[0155] Next, particles of a precursor seed crystal containing Me are grown in the above suspension at a pH of not less than 7 and not more than 8.5.

[0156] Then, the grown particles of the precursor seed crystal containing Me are mixed with a lithium raw material and a Q raw material, and then heat treated.

[0157] Examples of the Me raw material used in the preparation of the suspension include MeSO 4 、Me(NO 3 ) 2 、Me(CH 3 COO 2 And other compounds containing Me.

[0158] Examples of the alkaline compound used in the preparation of the suspension include Na 2 CO 3 , K 2 CO 3 、NaHCO 3 , KHCO 3 Carbonates and bicarbonates, etc.

[0159] For example, a Me source-containing solution A is prepared by dissolving a Me raw material containing Me in pure water at a predetermined concentration (e.g., 2 mol / L). In addition, a solution B containing a basic compound is prepared by dissolving a basic compound in pure water at a predetermined concentration (e.g., 2 mol / L). The two prepared solutions A and B are added dropwise to pure water while controlling the pH to be in the range of 7 or more and 8.5 or less, thereby obtaining a precursor seed crystal containing Me as a precursor. In the suspension containing the precursor seed crystal containing Me, the particles of the precursor seed crystal containing Me are grown while controlling the pH to be in the range of 7 or more and 8.5 or less.

[0160] Next, when producing a lithium composite oxide, a Li raw material, the above-mentioned Me-containing precursor seed particles as a precursor, and a Q raw material are prepared.

[0161] Examples of Li raw materials include Li 2 O. Li 2 O 2 Oxides, LiF, Li 2 CO 3 , LiOH and other salts, LiMeO 2 、LiMe 2 O 4 Lithium composite oxides, etc.

[0162] Examples of the Q raw material substance include lithium halide, transition metal halide, transition metal sulfide, transition metal nitride and the like.

[0163] For example, when Q is F, examples of the F raw material substance include LiF and transition metal fluorides.

[0164] These raw materials are weighed in a molar ratio shown in the composition formula (1). The weighed raw materials are mixed, for example, by a dry method or a wet method, and then heat-treated.

[0165] Through these steps, "x, y, α, and β" in the composition formula (1) are changed within the ranges shown by the composition formula (1).

[0166] The conditions of the heat treatment at this time are appropriately set so as to obtain the lithium composite oxide of Embodiment 1. The optimal conditions of the heat treatment vary depending on other production conditions and the target composition.

[0167] The temperature of the heat treatment can be appropriately changed within the range of, for example, 200 to 900° C. The time required for the heat treatment can be appropriately changed within the range of, for example, 1 minute to 20 hours. The atmosphere for the heat treatment can be an air atmosphere, an oxygen atmosphere, or an inert atmosphere such as nitrogen or argon.

[0168] In addition, the heat treatment may be performed in two or more stages, for example.

[0169] The temperature of the heat treatment may be, for example, in the range of 600 to 750° C. For example, when the heat treatment is performed in two stages, the temperature of the second stage of the heat treatment may be in the range of 600 to 750° C. By performing the heat treatment in such a temperature range, it is easy to synthesize a material having a BET specific surface area satisfying 5 m 2 / g or more and 10m 2 / g or less and an average particle size satisfying 3 μm or more and 30 μm or less.

[0170] As described above, by adjusting the raw materials used, the mixing conditions of the raw material mixture, and the heat treatment conditions, the lithium composite oxide constituting the positive electrode active material of the first embodiment can be substantially obtained.

[0171] Furthermore, as described above, the space group of the crystal structure of the obtained lithium composite oxide can be determined, for example, by X-ray diffraction measurement or electron beam diffraction measurement. Thus, for example, it can be confirmed that the obtained lithium composite oxide has a crystal structure belonging to space groups C2 / m and R3-m.

[0172] The average composition of the obtained lithium composite oxide can be determined by, for example, ICP emission spectroscopy, inert gas fusion-infrared absorption, ion chromatography, or a combination of these analytical methods.

[0173] (Implementation Method 2)

[0174] Hereinafter, Embodiment 2 will be described. Note that descriptions overlapping with those of Embodiment 1 described above will be appropriately omitted.

[0175] The battery of the second embodiment includes a positive electrode including the positive electrode active material of the first embodiment, a negative electrode, and an electrolyte.

[0176] According to the above technical configuration, a high-capacity battery can be realized.

[0177] In the battery of Embodiment 2, the positive electrode may include a positive electrode active material layer. In this case, the positive electrode active material layer may contain the positive electrode active material of Embodiment 1 as a main component (i.e., 50% or more (50% by mass) relative to the entire positive electrode active material layer).

[0178] According to the above technical configuration, a battery with a higher capacity can be realized.

[0179] Alternatively, in the battery of the second embodiment, the positive electrode active material layer may contain 70% or more (70% by mass or more) of the positive electrode active material of the first embodiment in terms of the mass ratio relative to the entire positive electrode active material layer.

[0180] According to the above technical configuration, a battery with a higher capacity can be realized.

[0181] Alternatively, in the battery of the second embodiment, the positive electrode active material layer may contain 90% or more (90% by mass or more) of the positive electrode active material of the first embodiment in terms of the mass ratio relative to the entire positive electrode active material layer.

[0182] According to the above technical configuration, a battery with a higher capacity can be realized.

[0183] The battery of Embodiment 2 can be configured as, for example, a lithium ion secondary battery, a nonaqueous electrolyte secondary battery, an all-solid battery, or the like.

[0184] That is, in the battery of Embodiment 2, the negative electrode may include, for example, a negative electrode active material capable of absorbing and releasing lithium ions. Alternatively, the negative electrode may include, for example, a material capable of dissolving and precipitating lithium metal as the negative electrode active material.

[0185] In the battery of Embodiment 2, the electrolyte may be, for example, a non-aqueous electrolyte (eg, a non-aqueous electrolytic solution).

[0186] In the battery of Embodiment 2, the electrolyte may be, for example, a solid electrolyte.

[0187] Figure 1 It is a cross-sectional view schematically showing the structure of a battery 10 as an example of a battery according to the second embodiment.

[0188] like Figure 1 As shown, the battery 10 includes a positive electrode 21 , a negative electrode 22 , a separator 14 , a case 11 , a sealing plate 15 , and a gasket 18 .

[0189] The separator 14 is disposed between the positive electrode 21 and the negative electrode 22 .

[0190] The positive electrode 21 , the negative electrode 22 , and the separator 14 are impregnated with, for example, a nonaqueous electrolyte (eg, a nonaqueous electrolytic solution).

[0191] An electrode group is formed by the positive electrode 21 , the negative electrode 22 , and the separator 14 .

[0192] The electrode group is housed in the case 11 .

[0193] The housing 11 is sealed by the gasket 18 and the sealing plate 15 .

[0194] The positive electrode 21 includes a positive electrode current collector 12 and a positive electrode active material layer 13 disposed on the positive electrode current collector 12 .

[0195] The positive electrode current collector 12 is made of, for example, a metal material (for example, at least one selected from aluminum, stainless steel, nickel, iron, titanium, copper, palladium, gold, and platinum, or an alloy thereof).

[0196] Furthermore, the positive electrode current collector 12 may be omitted and the case 11 may be used as the positive electrode current collector.

[0197] The positive electrode active material layer 13 contains the positive electrode active material of the first embodiment described above.

[0198] The positive electrode active material layer 13 may contain additives (eg, a conductive agent, an ion conductive aid, a binder, etc.) as necessary.

[0199] The negative electrode 22 includes a negative electrode current collector 16 and a negative electrode active material layer 17 disposed on the negative electrode current collector 16 .

[0200] The negative electrode current collector 16 is made of, for example, a metal material (for example, at least one selected from aluminum, stainless steel, nickel, iron, titanium, copper, palladium, gold, and platinum, or an alloy thereof).

[0201] Furthermore, the negative electrode current collector 16 may be omitted and the sealing plate 15 may be used as the negative electrode current collector.

[0202] The negative electrode active material layer 17 contains a negative electrode active material.

[0203] The negative electrode active material layer 17 may contain additives (eg, a conductive agent, an ion conductive aid, a binder, etc.) as necessary.

[0204] As the negative electrode active material, metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. can be used.

[0205] The metal material may be a single metal. Alternatively, the metal material may be an alloy. Examples of the metal material include lithium metal and lithium alloys.

[0206] Examples of the carbon material include natural graphite, coke, graphite mesophase carbon, carbon fiber, spherical carbon, artificial graphite, and amorphous carbon.

[0207] From the viewpoint of capacity density, silicon (Si), tin (Sn), silicon compounds, and tin compounds can be used as negative electrode active materials. The silicon compound and the tin compound may be in the form of an alloy or a solid solution.

[0208] Examples of silicon compounds include SiO x (where 0.05<x<1.95). Alternatively, SiO x A compound (alloy or solid solution) obtained by replacing a portion of silicon with other elements. Here, the other element refers to at least one selected from boron, magnesium, nickel, titanium, molybdenum, cobalt, calcium, chromium, copper, iron, manganese, niobium, tantalum, vanadium, tungsten, zinc, carbon, nitrogen and tin.

[0209] Examples of tin compounds include Ni2 Sn 4 Mg 2 Sn、SnO x (where 0<x<2), SnO 2 、SnSiO 3 etc. One tin compound selected from these may be used alone, or a combination of two or more tin compounds selected from these may be used.

[0210] The shape of the negative electrode active material is not particularly limited, and any negative electrode active material having a known shape (such as a particle shape or a fiber shape) can be used as the negative electrode active material.

[0211] In addition, the method for filling (absorbing) lithium in the negative electrode active material layer 17 is not particularly limited. As this method, specifically, there are (a) a method of depositing lithium in the negative electrode active material layer 17 by a gas phase method such as a vacuum evaporation method, and (b) a method of bringing a lithium metal foil into contact with the negative electrode active material layer 17 and heating both. Either method can diffuse lithium in the negative electrode active material layer 17 by heat. In addition, there is also a method of electrochemically absorbing lithium in the negative electrode active material layer 17. Specifically, a battery is assembled using a negative electrode 22 without lithium and a lithium metal foil (positive electrode). Then, the battery is charged so that the negative electrode 22 absorbs lithium.

[0212] As the binder of the positive electrode 21 and the negative electrode 22, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene-butadiene rubber, carboxymethyl cellulose, etc. can be used. In addition, as the binder, a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethane, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene can be used. In addition, a mixture of two or more materials selected from the above materials can also be used as a binder.

[0213] As the conductive agent of the positive electrode 21 and the negative electrode 22, graphite, carbon black, conductive fiber, graphite fluoride, metal powder, conductive whisker, conductive metal oxide, organic conductive material, etc. can be used. As examples of graphite, natural graphite and artificial graphite can be mentioned. As examples of carbon black, acetylene black, Ketjen black (registered trademark), channel black, furnace black, lamp black, thermal black can be mentioned. As examples of metal powder, aluminum powder can be mentioned. As examples of conductive whiskers, zinc oxide whiskers and potassium titanate whiskers can be mentioned. As examples of conductive metal oxides, titanium oxide can be mentioned. As organic conductive materials, phenylene derivatives can be mentioned.

[0214] Furthermore, a material that can be used as the conductive agent can be used to cover at least a portion of the surface of the binder. For example, the binder can be coated with carbon black. This can increase the capacity of the battery.

[0215] As the partition 14, a material having a large ion permeability and sufficient mechanical strength can be used. Examples of such materials include microporous films, woven fabrics, non-woven fabrics, and the like. Specifically, the partition 14 is preferably made of polyolefins such as polypropylene and polyethylene. The partition 14 made of polyolefins not only has excellent durability, but also can perform a shutdown function when overheated. The thickness of the partition 14 is, for example, in the range of 10 to 300 μm (or 10 to 40 μm). The partition 14 can be a single-layer film composed of one material. Alternatively, the partition 14 can be a composite film (or a multilayer film) composed of two or more materials. The porosity of the partition 14 is, for example, in the range of 30 to 70% (or 35 to 60%). "Porosity" refers to the proportion of the volume occupied by voids in the overall volume of the partition 14. "Porosity" is measured, for example, by mercury intrusion.

[0216] The nonaqueous electrolyte solution includes a nonaqueous solvent and a lithium salt dissolved in the nonaqueous solvent.

[0217] As the nonaqueous solvent, a cyclic carbonate solvent, a chain carbonate solvent, a cyclic ether solvent, a chain ether solvent, a cyclic ester solvent, a chain ester solvent, a fluorine solvent or the like can be used.

[0218] Examples of the cyclic carbonate solvent include ethylene carbonate, propylene carbonate, and butylene carbonate.

[0219] Examples of the chain carbonate solvent include dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.

[0220] Examples of the cyclic ether solvent include tetrahydrofuran, 1,4-dioxane, and 1,3-dioxolane.

[0221] Examples of the linear ether solvent include 1,2-dimethoxyethane and 1,2-diethoxyethane.

[0222] Examples of the cyclic ester solvent include γ-butyrolactone and the like.

[0223] Examples of the chain ester solvent include methyl acetate and the like.

[0224] Examples of the fluorinated solvent include fluoroethylene carbonate, fluoromethyl propionate, fluorobenzene, fluoroethyl methyl carbonate, and fluorodimethyl carbonate.

[0225] As the non-aqueous solvent, one non-aqueous solvent selected from these may be used alone, or as the non-aqueous solvent, a combination of two or more non-aqueous solvents selected from these may be used.

[0226] The non-aqueous electrolyte may contain at least one fluorine solvent selected from the group consisting of fluoroethylene carbonate, fluoromethyl propionate, fluorobenzene, fluoroethyl methyl carbonate, and fluorodimethyl carbonate.

[0227] When these fluorinated solvents are contained in the non-aqueous electrolyte, the oxidation resistance of the non-aqueous electrolyte is improved.

[0228] As a result, even when the battery 10 is charged with a high voltage, the battery 10 can be operated stably.

[0229] In the battery of Embodiment 2, the electrolyte may be a solid electrolyte.

[0230] As the solid electrolyte, an organic polymer solid electrolyte, an oxide solid electrolyte, a sulfide solid electrolyte, or the like can be used.

[0231] As the organic polymer solid electrolyte, for example, a compound of a polymer compound and a lithium salt can be used.

[0232] The polymer compound may have an ethylene oxide structure. By having an ethylene oxide structure, a large amount of lithium salt can be contained, and the ion conductivity can be further improved.

[0233] As the oxide solid electrolyte, for example, LiTi 2 (PO 4 ) 3 NASICON solid electrolytes represented by their element substitution products, (LaLi)TiO 3 Perovskite-type solid electrolytes based on Li 14 ZnGe 4 O 16 , Li 4 SiO 4 、LiGeO 4 LISICON solid electrolytes represented by their element substitution bodies, Li 7 La 3 Zr2 O 12 Garnet-type solid electrolytes represented by their element substitution bodies, Li 3 N and its H substitution, Li 3 PO 4 and its N-substituted form, etc.

[0234] As the sulfide solid electrolyte, for example, Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2 SB 2 S 3 , Li 2 S-GeS 2 , Li 3.25 Ge 0.25 P 0.75 S 4 , Li 10 G 2 S 12 In addition, LiX (X: F, Cl, Br, I), MO y , Li x MO y (M: any one of P, Si, Ge, B, Al, Ga, and In) (x, y: natural numbers), etc.

[0235] Among these, sulfide solid electrolytes are particularly good in formability and have high ion conductivity. Therefore, by using sulfide solid electrolytes as solid electrolytes, batteries with higher energy density can be realized.

[0236] In addition, in sulfide solid electrolytes, Li 2 SP 2 S 5 The electrochemical stability is high and the ion conductivity is higher. Therefore, if Li 2 SP 2 S 5 As a solid electrolyte, it can achieve batteries with higher energy density.

[0237] Furthermore, the solid electrolyte layer may contain the above-mentioned nonaqueous electrolyte solution.

[0238] When the solid electrolyte layer contains a non-aqueous electrolyte, lithium ions can be easily transferred between the active material and the solid electrolyte, thereby achieving a battery with a higher energy density.

[0239] In addition, the solid electrolyte layer may contain a gel electrolyte, an ionic liquid, or the like in addition to the solid electrolyte.

[0240] The gel electrolyte may be a gel electrolyte containing a non-aqueous electrolyte in a polymer material. As the polymer material, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond may be used.

[0241] The cations constituting the ionic liquid may be aliphatic chain quaternary salts such as tetraalkylammonium and tetraalkylphosphonium, aliphatic cyclic ammonium such as pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium, piperidinium, etc., nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium, etc. The anions constituting the ionic liquid may be PF 6 - , BF 4 - , SbF 6 - , AsF 6 - 、SO 3 CF 3 - 、N(SO 2 CF 3 ) 2 - 、N(SO 2 C 2 F 5 ) 2 - 、N(SO 2 CF 3 )(SO 2 C 4 F 9 ) - , C(SO 2 CF 3 ) 3 - etc. In addition, the ionic liquid may contain a lithium salt.

[0242] As the lithium salt, LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiSO 3 CF 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 、LiN(SO 2 CF 3 )(SO 2 C4 F 9 )、LiC(SO 2 CF 3 ) 3 As the lithium salt, one lithium salt selected from these may be used alone. Alternatively, as the lithium salt, a mixture of two or more lithium salts selected from these may be used. The concentration of the lithium salt is, for example, in the range of 0.5 to 2 mol / liter.

[0243] The battery of the second embodiment can be configured as a battery in various shapes such as a coin-shaped, cylindrical, square, sheet-shaped, button-shaped, flat, and laminated type.

[0244] (Example)

[0245] <Example 1>

[0246] [Preparation of positive electrode active material]

[0247] MnSO 4 、NiSO 4 and CoSO 4 The raw materials were weighed at a molar ratio of Mn / Ni / Co = 6.0 / 2.0 / 2.0. The obtained raw materials were dissolved in pure water at a concentration of Mn+Ni+Co of 2 mol / L to obtain a solution containing Mn, Ni and Co (i.e., a solution containing Me raw material). In addition, in another container, KHCO 3 KHCO 3 The concentration is 2 mol / L and dissolved in pure water to obtain KHCO 3 Solution.

[0248] Next, 500 mL of pure water was prepared in a 1 L reaction vessel equipped with an overflow tube. A solution containing the Me raw material was dripped into the pure water at 0.7 mL / min, and KHCO 3 The solution was kept at a pH of 7.5. The liquid temperature was kept at 60°C, and the Me raw material and KHCO 3 The reaction lasted for 8 hours.

[0249] After the reaction, the solution remaining in the reaction container was recovered. The recovered solution was washed, filtered, and vacuum dried at 120° C. for 12 hours. Thus, MeCO, a precursor of the positive electrode active material, was obtained. 3 .

[0250] The obtained precursor, Li 2 CO 3 and LiF were weighed at a molar ratio of Li / Mn / Co / Ni / O / F=1.166 / 0.5 / 0.167 / 0.167 / 1.917 / 0.083.

[0251] Then, as a first stage of heat treatment, the obtained mixture was heat treated at 400° C. in an air atmosphere for 10 hours.

[0252] Next, as a second step of heat treatment, the obtained mixture was heat treated at 700° C. in an air atmosphere for 10 hours.

[0253] In this way, a lithium composite oxide was obtained. This lithium composite oxide was used as the positive electrode active material of Example 1.

[0254] The obtained positive electrode active material was subjected to powder X-ray diffraction measurement, thereby analyzing the crystal structure of the lithium composite oxide constituting the positive electrode active material.

[0255] The obtained lithium composite oxide constituting the positive electrode active material is a two-phase mixture of a first phase having a crystal structure belonging to the space group C2 / m and a second phase having a crystal structure belonging to the space group R-3m.

[0256] The average composition of the lithium composite oxide of Example 1 obtained from the molar ratio of the raw materials is shown in Table 1. 1.16 6 Mn 0.5 Co 0.167 Ni 0.167 O 1.917 F 0.083 express.

[0257] The BET specific surface area, average particle diameter and average crystallite size of the obtained positive electrode active material, ie, lithium composite oxide, were determined. The results are shown in Table 1. The BET specific surface area, average particle diameter and average crystallite size were determined as follows.

[0258] Figure 2 This is a SEM image of the positive electrode active material of Example 1.

[0259] (BET specific surface area)

[0260] The BET specific surface area of ​​the obtained positive electrode active material, namely the lithium composite oxide, was measured. The measurement was performed using a nitrogen adsorption and desorption device AUTOSORB-3 (Yuasiionix Co., Ltd.). 50 mg of the lithium composite oxide was weighed, sealed in a measurement cell, and vacuum dried at 150°C for 4 hours, and then measured while cooling with liquid nitrogen.

[0261] (Average particle size)

[0262] The SEM image of the obtained positive electrode active material, namely the lithium composite oxide, was obtained. The measurement was performed using JSM-6700F (JEOL Ltd.). The particle sizes of 100 particles of the lithium composite oxide were measured using the SEM image. The average particle size was calculated from the measurement results.

[0263] (Average crystallite size)

[0264] The crystallite size of the lithium composite oxide, which is the obtained positive electrode active material, was measured using an X-ray diffraction device MiniFlex (RIGAKU Co., Ltd.). The crystallite size was measured at 5 locations, and the average value was taken as the "average crystallite size."

[0265] [Battery production]

[0266] 70 parts by mass of the above-mentioned positive electrode active material, 20 parts by mass of a conductive agent, 10 parts by mass of polyvinylidene fluoride (PVDF) and an appropriate amount of 2-methylpyrrolidone (NMP) were mixed to obtain a positive electrode mixture slurry.

[0267] The positive electrode mixture slurry was applied to one side of a positive electrode current collector formed of a 20 μm thick aluminum foil.

[0268] The positive electrode mixture slurry was dried and rolled to obtain a positive electrode plate having a positive electrode active material layer and a thickness of 60 μm.

[0269] The obtained positive electrode plate was punched into a circular shape with a diameter of 12.5 mm, thereby obtaining a positive electrode.

[0270] Separately, a lithium metal foil having a thickness of 300 μm was punched into a circular shape having a diameter of 14.0 mm, thereby obtaining a negative electrode.

[0271] Separately, fluoroethylene carbonate (FEC), ethylene carbonate (EC), and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 1:1:6 to obtain a non-aqueous solvent.

[0272] In the non-aqueous solvent, LiPF 6 It was dissolved at a concentration of 1.0 mol / liter, thereby obtaining a non-aqueous electrolyte solution.

[0273] The obtained non-aqueous electrolyte was allowed to permeate into a separator (manufactured by Celgard Co., Ltd., Model 2320, thickness 25 μm). This separator was a three-layer separator consisting of a polypropylene layer, a polyethylene layer, and a polypropylene layer.

[0274] Using the positive electrode, negative electrode, and separator described above, a coin-type battery of CR2032 specification was produced in a dry box whose dew point was controlled at -50°C.

[0275] <Examples 2 and 3>

[0276] In Example 1, the second stage heating temperature was changed to the heating temperature shown in Table 1. A lithium composite oxide having the same average composition as Example 1 was synthesized in the same manner as Example 1. This lithium composite oxide was used as the positive electrode active material in Examples 2 and 3.

[0277] The obtained positive electrode active material was subjected to powder X-ray diffraction measurement. The crystal structure of the lithium composite oxide constituting the positive electrode active material was analyzed. As a result, the lithium composite oxide constituting the positive electrode active material of Examples 2 and 3 was a two-phase mixture of a first phase having a crystal structure belonging to the space group C2 / m and a second phase having a crystal structure belonging to the space group R-3m.

[0278] The BET specific surface area, average particle diameter, and average crystallite size of the obtained positive electrode active material, ie, lithium composite oxide, were determined in the same manner as in Example 1. The results are shown in Table 1.

[0279] Using the obtained positive electrode active material, coin-type batteries of Examples 2 and 3 were prepared in the same manner as in Example 1.

[0280] <Comparative Example 1>

[0281] By using a known method, a mixture of lithium carbonate and cobalt oxide is calcined to obtain a solid phase method having a LiCoO 2 Represents the composition of the positive electrode active material.

[0282] The obtained positive electrode active material was subjected to powder X-ray diffraction measurement. Thus, the crystal structure of the lithium composite oxide constituting the positive electrode active material of Comparative Example 1 was analyzed. As a result, the lithium composite oxide constituting the positive electrode active material of Comparative Example 1 was a single phase having only a crystal structure belonging to the space group R-3m.

[0283] The average particle size of the obtained positive electrode active material, ie, lithium composite oxide, was determined by the same method as in Example 1. The results are shown in Table 1.

[0284] A coin-type battery of Comparative Example 1 was produced in the same manner as in Example 1 using the obtained positive electrode active material.

[0285] <Comparative Example 2>

[0286] Using the known coprecipitation method, a Mn 0.357 Co 0.143 Ni 0.143 OH 2Next, the obtained precursor was heat treated under the same heating conditions as in Example 1 to synthesize a lithium composite oxide having the same average composition as in Example 1. This lithium composite oxide was used as the positive electrode active material of Comparative Example 2.

[0287] The obtained positive electrode active material was subjected to powder X-ray diffraction measurement. Thus, the crystal structure of the lithium composite oxide constituting the positive electrode active material was analyzed. As a result, the lithium composite oxide constituting the positive electrode active material of Comparative Example 2 was a two-phase mixture of a first phase having a crystal structure belonging to the space group C2 / m and a second phase having a crystal structure belonging to the space group R-3m.

[0288] The BET specific surface area, average particle diameter, and average crystallite size of the obtained positive electrode active material, ie, lithium composite oxide, were determined in the same manner as in Example 1. The results are shown in Table 1.

[0289] A coin-type battery of Comparative Example 2 was produced in the same manner as in Example 1 using the obtained positive electrode active material.

[0290] <Comparative Examples 3 to 6>

[0291] The lithium composite oxides of Comparative Examples 3 to 6 were synthesized in the same manner as in Example 1 except that the heating temperature in the second stage was changed. Specifically, the heating temperature was adjusted within the range of 300 to 1000° C. Table 1 shows the heating temperature in the second stage of Comparative Examples 3 to 6.

[0292] The obtained positive electrode active material was subjected to powder X-ray diffraction measurement. Thus, the crystal structure of the lithium composite oxide constituting the positive electrode active material of Comparative Examples 3 to 6 was analyzed. As a result, the lithium composite oxide constituting the positive electrode active material of Comparative Examples 3 to 6 was a two-phase mixture of a first phase having a crystal structure belonging to the space group C2 / m and a second phase having a crystal structure belonging to the space group R-3m.

[0293] For the positive electrode active materials of Comparative Examples 3 to 6, namely, the lithium composite oxides, the BET specific surface area, the average particle diameter and the average crystallite size were determined in the same manner as in Example 1. The results are shown in Table 1.

[0294] Using the positive electrode active materials of Comparative Examples 3 to 6, coin-type batteries of Comparative Examples 3 to 6 were produced in the same manner as in Example 1.

[0295] <Battery Evaluation>

[0296] The current density at the positive electrode was set to 0.5 mA / cm 2 , the battery of Example 1 is charged until the voltage reaches 4.7V.

[0297] Then, the discharge end voltage was set to 2.5 V and the discharge current was increased to 0.5 mA / cm 2 The battery of Example 1 was discharged at a current density of .

[0298] The initial discharge capacity of the battery of Example 1 is 274 mAh / g.

[0299] The initial discharge capacity of the coin-type batteries of Examples 2 and 3 and Comparative Examples 2 to 6 was measured by the same method as in Example 1. Table 1 shows the initial discharge capacity of the batteries of Examples 2 and 3 and Comparative Examples 2 to 6.

[0300] The battery of Comparative Example 1 was evaluated in the following manner.

[0301] The current density at the positive electrode was set to 0.5 mA / cm 2 The battery of Comparative Example 1 was charged until the voltage reached 4.3V.

[0302] Then, the discharge end voltage was set to 2.5 V and the discharge current was increased to 0.5 mA / cm 2 The battery of Comparative Example 1 was discharged at a current density of .

[0303] The initial discharge capacity of the battery of Comparative Example 1 was 150 mAh / g.

[0304] The above results are shown in Table 1.

[0305] Table 1

[0306]

[0307] As shown in Table 1, the batteries of Examples 1 to 3 have an initial discharge capacity of 240 to 274 mAh / g. Among them, the initial discharge capacity of the battery of Example 1 is the highest. On the other hand, the initial discharge capacity of the batteries of Comparative Examples 1 to 6 is 51 to 221 mAh / g. As such, the batteries of Examples 1 to 3 have a higher initial discharge capacity than the batteries of Comparative Examples 1 to 6.

[0308] The reason for this is that the lithium composite oxides constituting the positive electrode active material of Examples 1 to 3 have a BET specific surface area satisfying 5 m 2 / g or more and 10m 2 / g or less, and the average particle size satisfies the range of 3 μm or more and 30 μm or less. In addition, the lithium composite oxides constituting the positive electrode active material of Examples 1 to 3 also have an average crystallite size satisfying Above and The following range.

[0309] As described above, the lithium composite oxides constituting the positive electrode active material of Examples 1 to 3 satisfy both a large BET specific surface area and a large average particle size. When a lithium composite oxide with a large BET specific surface area is used as the positive electrode active material, the Li diffusion length becomes shorter, which is conducive to high capacity. In addition, when a lithium composite oxide with a large average particle size is used as the positive electrode active material, high filling can be achieved and high capacity can be achieved. In the lithium composite oxides of Examples 1 to 3, both a large BET specific surface area and a large average particle size are achieved, so high capacity can be achieved.

[0310] The lithium composite oxides constituting the positive electrode active materials of Comparative Examples 2, 5 and 6 have a large average particle size but a small BET specific surface area. Therefore, in the positive electrode active materials of Comparative Examples 2, 5 and 6, the Li diffusion length becomes long, making it difficult to achieve a high capacity.

[0311] Furthermore, the lithium composite oxides constituting the positive electrode active material of Comparative Examples 3 and 4 have an average particle size in the range of 3 μm or more and 30 μm or less and also satisfy a large BET specific surface area. 2 When the value of / g is too large, it is not convenient to achieve high filling when actually manufacturing the battery. As a result, it is difficult to achieve high capacity in the batteries of Comparative Examples 3 and 4, and the initial discharge capacity is smaller than that of the battery of Example 1.

[0312] Furthermore, the lithium composite oxide constituting the positive electrode active material of Comparative Example 1 has an average particle size of less than 3 μm. Therefore, the battery of Comparative Example 1 cannot achieve a high filling of the positive electrode active material, and the initial discharge capacity is greatly reduced.

[0313] In addition, when the average crystallite size is too large, the Li diffusion length becomes long, which is not conducive to high capacity. On the other hand, when the average crystallite size is too small, the positive electrode active material does not fully grow crystals, which is not conducive to high capacity. The average crystallite size that can achieve high capacity is Above and The average crystallite size of the lithium composite oxide of Example 1 satisfies Above and Therefore, the battery of Example 1 can achieve a further high capacity.

[0314] Industrial Availability

[0315] The positive electrode active material disclosed herein can be used as a positive electrode active material for batteries such as secondary batteries.

Claims

1. A positive electrode active material comprising a lithium composite oxide having a crystal structure belonging to a layered structure, In the lithium composite oxide, the BET specific surface area is 5m 2 / g or more and 10m 2 / g or less, and an average particle size of 3 μm or more and 30 μm or less, In the lithium composite oxide, the average crystallite size calculated by X-ray diffraction using the peak reflecting the (003) plane is Above and the following, The lithium composite oxide contains at least one selected from F, Cl, N, and S.

2. The positive electrode active material according to claim 1, In the lithium composite oxide, the average particle size is 10 μm or more and 30 μm or less.

3. The positive electrode active material according to claim 1 or 2, The lithium composite oxide has a BET specific surface area of ​​7.5 m 2 / g or more and 8.1m 2 / g or less.

4. The positive electrode active material according to claim 1 or 2, The lithium composite oxide contains Mn.

5. The positive electrode active material according to claim 1 or 2, The lithium composite oxide contains F.

6. The positive electrode active material according to claim 1 or 2, The average composition of the lithium composite oxide is represented by the following composition formula (1): Li x Me y O α Q β ··· Formula (1) in, The Me is at least one selected from the group consisting of Mn, Co, Ni, Fe, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si, P and Al, The Q is at least one selected from F, Cl, N and S, and The composition formula (1) satisfies the following conditions: 1.05≤x≤1.5, 0.6≤y≤1.0, 1.2≤α≤2.0 and 0<β≤0.

8.

7. The positive electrode active material according to claim 6, The Me includes at least one selected from the group consisting of Mn, Co, Ni, Fe, Cu, V, Ti, Cr and Zn.

8. The positive electrode active material according to claim 6, The Me includes at least one selected from the group consisting of Mn, Co, Ni and Al.

9. The positive electrode active material according to claim 7, The Me includes Mn.

10. The positive electrode active material according to claim 9, The ratio of the Mn to the Me is 59.9 mol % or more.

11. The positive electrode active material according to claim 6, Said Q comprises F.

12. The positive electrode active material according to claim 1 or 2, The lithium composite oxide is contained as a main component.

13. The positive electrode active material according to claim 1 or 2, The lithium composite oxide is a multiphase mixture including a first phase having a crystal structure belonging to a space group C2 / m and a second phase having a crystal structure belonging to a space group R-3m.

14. The positive electrode active material according to claim 13, The lithium composite oxide is a two-phase mixture of the first phase and the second phase.

15. A battery comprising a positive electrode, a negative electrode and an electrolyte. The positive electrode includes the positive electrode active material according to any one of claims 1 to 14.

16. The battery according to claim 15, The negative electrode includes a negative electrode active material capable of absorbing and releasing lithium ions, or a material capable of dissolving and precipitating lithium metal as a negative electrode active material. The electrolyte is a non-aqueous electrolyte.

17. The battery according to claim 15, The negative electrode includes a negative electrode active material capable of absorbing and releasing lithium ions, or a material capable of dissolving and precipitating lithium metal as a negative electrode active material. The electrolyte is a solid electrolyte.

Citation Information

Patent Citations

  • Positive electrode active material for secondary battery and secondary battery including the same

    JP2018521456A

  • Positive electrode active material

    CN105247709A

  • Positive electrode active material and battery

    CN109309210A

  • Positive electrode active material and battery

    CN110048089A